From grass roots to world class (A strategy for delivering physical activity) - Kiraly, I. A.; Gál, A. (Physical Culture and Sport. Studies and Research, 2011)
During the 2008 Beijing Olympic Games, the Hungarian sports team`s performance was worse than expected by most of the Hungarian people and the leaders of the Hungarian sports establishment. The Hungarian athletes returned home with a much lower medal tally than in previous decades. More than two years have elapsed since the Olympic Games, but instead of analysing the real reasons for the poor performance, most of the debates in Hungary are about whether we will restore our reputation by taking 8-10 gold medals in the 2012 London Olympics. People in the United Kingdom are also full of hope for a great medal tally in London, not just because of the "home team advantage" but also by reason of the UK`s outstanding performance in 2008. The British team finished fourth in the final medal table at the Beijing Olympic Games despite their poor performance one-and-half decades ago in Atlanta, surprising not just the British but also the whole world. By this time, the British strategy was to invest not just in elite sports but also in grass-roots participation sports. If Hungary wants to enhance its elite sports, it must engage in similar changes. It is clear from the latest data that the Hungarian XXI Sports Strategy`s aim of making Hungary a sporting nation seems an illusion. Participation sports, which are the foundation of national sporting success and provide the future talents for the elite sports sector, are in need of urgent and substantive reform. By means of secondary analyses and document analyses this article discusses the current state of British sport using the latest data. It then examines recent reforms in English participation sports as well as the latest sports strategy in England and its objectives. In all this, it makes comparison with what is happening in Hungary. The upshot is that Hungary and Britain differ at many points throughout the whole process, from strategy planning to implementation. These contrasts explain the differences in the effectiveness of the British and Hungarian processes. We hope that the outcome of this examination of the efficient Western European process and its comparison with the unsuccessful Hungarian system will assist those responsible for the development of participation sports and elite sports in Hungary.